Trail-laying behaviour as a function of resource quality in the ant Camponotus rufipes - Schilman, Pablo Ernesto (2011)
Chemical trails have been shown to act as an orientation cue in some ant species. Here, I report that the trail-laying behaviour in the nectar-feeding ant, Camponotus rufipes, varies with the concentration of the sucrose solutions collected. Single workers collected solutions of different sucrose concentrations (5, 20, and 40 in weight) during 4 consecutive visits to the resource, and their trail-marking behaviour was recorded on soot-coated slides during their first and last visits. Results suggest that these chemical trails provide both an orientation cue between the nest and the food source, as previously suggested for Camponotus ants, as well as information about food quality.